PERAN PENGAMPUNAN PAJAK (TAX AMNESTY) DALAM PENCAPAIAN TARGET PENERIMAAN PAJAK KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAKARTA SELATAN II - Edy Edy; Taufik Sliffian; Radityo Nugroho (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
Tax amnesty is a government effort to increase excavation of potential taxation that is still lacking. This study aims to determine the role of tax amnesty and the efforts made to achieve the tax revenue target in the South Jakarta Regional Directorate General of Taxes II, by conducting interviews and interviews with the person in charge of tax amnesty activities and comparing them with regulations that discuss the process. It turns out that through the efforts made, tax amnesty has a role in achieving tax revenue targets even though there are obstacles but not significant obstacles. Overall the process of implementing tax amnesty runs in accordance with applicable laws in Indonesia.